2019
DOI: 10.3389/fphys.2019.00202
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physical Activity on Cognitive Performance in an Italian Elementary School: Insights From a Pilot Study Using Structural Equation Modeling

Abstract: When compared to the previous generations, younger generations have become sedentary on a global level. Physical activity positively contributes to human growth and development, causing, indeed, both physiological and psychological benefits. The aim of the current study was examining the relationship between physical activity and school achievement in a sample of 80 Italian elementary (viz. primary) school last year responding children (11.0 ± 0.3 years, 1.46 ± 0.09 m, 39.5 ± 7.9 kg). Such an aim was fulfilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 53 publications
0
34
0
6
Order By: Relevance
“…One branch of physical fitness is called musculoskeletal fitness, which stands for motor fitness, muscular strength, flexibility, and muscular endurance [3]. Among youth, different levels of musculoskeletal fitness have been conditioned by physical education (PE) in schools [4], which aims to incorporate activities for enhancing children's physical fitness level [5].…”
Section: Introductionmentioning
confidence: 99%
“…One branch of physical fitness is called musculoskeletal fitness, which stands for motor fitness, muscular strength, flexibility, and muscular endurance [3]. Among youth, different levels of musculoskeletal fitness have been conditioned by physical education (PE) in schools [4], which aims to incorporate activities for enhancing children's physical fitness level [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is important that girls and young women participate in sports and develop skills that promote lifelong athletic participation, because of the psychological, sociologic [10], and physiological benefits associated with exercise [11].…”
Section: Introductionmentioning
confidence: 99%
“…Hraste et al [ 5 ] examined the efficiency of an integrated mathematics/geometry and physical activity program and found its effectiveness. In addition, Padulo et al [ 6 ] found that fundamental motor skills such as jump or run correlated to cognitive achievement in areas such as English, mathematics, sport, and technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The physical opportunities offered at school and at home are important settings for improving children’s physical and psychological-cognitive status [ 6 ] and for facilitating development. Campos et al [ 7 ] showed the similarity in motor progress in children in the first months of schooling; however, this diverges as children grow older.…”
Section: Introductionmentioning
confidence: 99%